PENGEMBANGAN MODEL PEMBELAJARAN “PROMISTER” UNTUK MENINGKATKAN HASIL BELAJAR WAYANG PANDHAWA PADA SISWA SEKOLAH DASAR - Istiningsih, Galih; Alawiyah, Ela Minchah; Priharlina, Evik (Universitas Muhammadiyah Jakarta, 2018)
ABSTRACTThis study departs from the problem of the still low quality of the process of learning Javanese language, one of which is the wayang pandhawa and the ability of the teacher to integrate character values in classroom learning. The main objective of this year I study was to produce innovative learning models based on Multiple Character Intelligence (PROMISTER) projects that had obtained material and learning expert validation.Research uses research and development methods or